STRATEGI PENINGKATAN KUALITAS KAMPUNG KOTA PADA PROGRAM KAMPUNG KREATIF DAN BEBAS SAMPAH DI KAMPUNG DAGO POJOK DAN KAMPUNG BANDUNG KIDUL - Ade Wahyudi; Iwan Kustiwan (Jurusan Teknik Perencanaan Wilayah dan Kota, Fakultas Sains dan Teknologi, Universitas Islam Negeri Alauddin Makassar, 2019)
The increasing number of population’s growth become the main factors causing the informal settlement exists in the urban area. Most of low income people are living in Urban Villages. Urban village generally located in the heart city and at the same times makes the city more compex and congested, crowded, polluted and unable to accommodate and perform the needs of housing provision. This conditions lowering the settlement quality. Moreover, the majority on housing delivery system in Indonesia administered by individual plans and lack of access to a proper resources. This research aims to analyze the level of participation and formulating the strategy to increase human settlement quality. This research adopted quantitative descriptive analysis by multiple regression and tribina analysis. The result showed that the level of participation in Kampung Bandung Kidul with Zero Waste program are still low and because below than 50% citizen participated in prepadness, planning, implementation and evaluation and benefit. Otherwise, In Kampung Dago Pojok, the level of community participation are in medium and above 50% of community participated on Youth Creativity Kampung. Tribina analysis adopted to formulate the strategy of participation in both urban villages to improve the housing quality.